Restricting Public Officials’ Authority to Combat Corruption: The Role of Term Limits and Political Sanctions in Indonesia - Fatimah, Siti; Beck , Martha Catherine; Sert, Hüseyin Emin; Alfarisi, Muhammad Adib (Journal of Indonesian Legal Studies, 2025)
Corruption among public officials continues to pose a serious threat to the integrity and sustainability of democratic governance in Indonesia. This study examines the restriction of public officials’ authority, particularly through political term limits and the revocation of political rights for convicted officials, as a preventive strategy against corruption. Employing a normative legal research method and document analysis, the study analyzes Indonesian laws, policies, and case data from regional heads between 2004 and 2019. The findings reveal recurring patterns of power abuse and highlight the social and institutional consequences of corruption. The study also identifies challenges in implementing anti-corruption policies, emphasizing the need for systemic reforms to enhance transparency and accountability. The results suggest that political term limits can reduce opportunities for previously corrupt individuals to regain office and help restore public confidence in governmental institutions. The study concludes that effectively combating corruption requires coordinated efforts among government bodies, civil society, and law enforcement agencies to implement policies that reinforce integrity and institutional accountability.